2012
DOI: 10.1007/s00217-012-1693-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of iodine bioavailability from chicken eggs versus iodized kitchen salt with in vitro method

Abstract: The goal of the presented studies was to investigate speciation and bioavailability of iodine from chicken eggs versus iodized kitchen salt with an in vitro method. Determination of iodine total content in chicken eggs and iodized kitchen salt was carried out by inductively coupled plasma mass spectrometry (ICP MS). The majority of iodine was accumulated in the yolk-the concentration was even 37 times higher than in white. Chicken eggs were treated with buffer (Tris HCl pH = 7.5) and enzymatic extraction media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Together with other iodine containing food Wagner et al 2009), the UL of 500 mg I/d (D-A-CH 2008) or 1000 mg I/d (WHO 1994) can be reached easily. Nevertheless, from an in vitro study was concluded that the bioavailability of iodine from eggs amounted to about 30% only (Lipiec et al 2012). But to verify this result and to derive final conclusions, more in vivo studies on this issue are necessary.…”
Section: Eggsmentioning
confidence: 73%
“…Together with other iodine containing food Wagner et al 2009), the UL of 500 mg I/d (D-A-CH 2008) or 1000 mg I/d (WHO 1994) can be reached easily. Nevertheless, from an in vitro study was concluded that the bioavailability of iodine from eggs amounted to about 30% only (Lipiec et al 2012). But to verify this result and to derive final conclusions, more in vivo studies on this issue are necessary.…”
Section: Eggsmentioning
confidence: 73%
“…thyroid hormones, high molecular weight proteins). [3][4][5] In food with a plant origin, such as forage, hay or vegetables, iodine is primarily present in form of iodide. [6] The bioavailability of iodide for mammals is 96%, while the bioavailability of organic species, such as monoiodotyrosine (MIT), is only 80%.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Moreover, iodide can be found in body fluids, such as blood, urine, sweat or breast milk, and in the case of birds also in eggs. [4,15] KEYWORDS Iodine; speciation; animal tissue; ICP-MS; size-exclusion chromatography OPEN ACCESS sample preparation were used almost exclusively for the determination of the total iodine content. [3,8,34,35] Only two papers concerning iodine speciation in animal tissue samples were recently published.…”
Section: Introductionmentioning
confidence: 99%
“…Nobias Chelate PB-1 and, more effectively, InertSep ME-1 were used to remove nearly 100% Mo, Sn and Zr from samples at pH 7. Comparison of I speciation and bioavailability between iodized salt and chicken eggs was carried out by Lipiec et al 134 A two-stage simulated digestion (pepsin followed by pancreatin) of both egg yolk and albumin was devised and I determined by SEC-ICP-MS. Yolk contained 37-times more I than the white while the bioavailability from the former was 10% and from the white it was 33%; this is in contrast to 100% availability of I À in kitchen salt. However, the bioavailability from egg yolk decreased with cooking indicating I remains bound to non-digestible, coagulated and insoluble proteins.…”
Section: Applications: Drugs and Pharmaceuticals Traditional Medicinmentioning
confidence: 99%